2014
DOI: 10.1016/j.carbon.2014.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Double-walled carbon nanotubes: Quantitative purification assessment, balance between purification and degradation and solution filling as an evidence of opening

Abstract: We compared the effect of different oxidizing agents on purification, functionalization and opening of double-walled carbon nanotubes. The oxidative treatments were realized in nitric acid solutions at different concentrations (3 M or 15 M), in a mixture of two oxoacids (conc. HNO 3 /conc. H 2 SO 4) or in sulphuric acid solutions of KMnO 4 or K 2 Cr 2 O 7. Most of these treatments were very efficient for purification (removal of residual catalytic metal nanoparticles and/or of disorganized carbon) but also cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 49 publications
4
53
0
Order By: Relevance
“…Typical images show graphene in a form that could be described as carbon veils or a crumpled FLG particle, with marked curvatures (arrowed in Fig. 4) which could reveal that it was wrapped, at least partly, around the MgO grains, in agreement with observations of other acid-treated samples [53,58]. Obviously this is very different from the classical CVD deposition on planar substrates where the graphene domain size can be easily measured.…”
Section: Powderssupporting
confidence: 78%
“…Typical images show graphene in a form that could be described as carbon veils or a crumpled FLG particle, with marked curvatures (arrowed in Fig. 4) which could reveal that it was wrapped, at least partly, around the MgO grains, in agreement with observations of other acid-treated samples [53,58]. Obviously this is very different from the classical CVD deposition on planar substrates where the graphene domain size can be easily measured.…”
Section: Powderssupporting
confidence: 78%
“…This sample was denoted pDWCNTs. The pDWCNTs were oxidized using a two stage process widely studied by Bortolamiol et al [40]. Firstly, a sample was refluxed in 3 M HNO 3 at 130°C for 24 h and then treated by a mixture of 15 M HNO 3 and 18 M H 2 SO 4 (volume ratio is 1:3) at 70°C for 5 h. The oxidized sample, denoted ox DWCNTs, was washed by deionized water three times to neutral pH and dried at 100°C for 24 h. Fluorination of ox DWCNTs and pDWCNTs was performed in a Teflon flask with gaseous BrF 3 diluted by vapors of Br 2 at room temperature for 3 days according to the method described in [41].…”
Section: Methodsmentioning
confidence: 99%
“…The sample was refluxed at 130 C in 3 M HNO 3 for 24 h followed by a treatment at 70 C in 1:3 vol. solution of 15 M HNO 3 and 18 M H 2 SO 4 for 5 h. It has been shown that this procedure allows removal of disordered carbon and additionally functionalizes the DWCNTs walls by oxygen containing groups [34].…”
Section: Synthesismentioning
confidence: 99%